INFLUENCE OF SOCIAL MEDIA MARKETING, ELECTRONIC WORD OF MOUTH AND CONSUMER ENGAGEMENT TO BRAND LOYALTY IN INDONESIA GRAB COMPANY - Bismoaziiz; Usep Suhud; Saparuddin (International Journal of Business and Social Science Research, 2021)
This study aims to analyze social media marketing, electronic word of mouth, and consumer attachment to brand loyalty in Grab Indonesia. The research design used is quantitative research with a causal approach that examines the effect of exogenous variables (social media marketing, electronic word of mouth, and consumer attachment) on endogenous variables (brand loyalty). The population in this study were consumers of social media followers (Instagram) grab with an infinite number, therefore sampling was carried out using purposive sampling with the consideration of respondents as followers of Instagram grab with a minimum period of following is 6 months and has given "likes" to the grab Instagram posts. The sample used in this study were consumers of online transportation companies (grab) as many as 300 respondents. This research analysis tool uses a structural equation model (SEM). The results showed that the exogenous variables (social media marketing, electronic word of mouth, and consumer attachment) positively and significantly affect endogenous variables (brand loyalty). The variable that has the highest value in influencing brand loyalty is social media marketing. Meanwhile, the variable that directly influences brand loyalty with the lowest regression coefficient is electronic word of mouth.